2019
DOI: 10.4049/jimmunol.1801425
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept Targets T Follicular Helper and Regulatory T Cells, Disrupting Molecular Pathways That Regulate Their Proliferation and Maintenance

Abstract: Abatacept is a CTLA-4-Ig fusion protein that binds to the costimulatory ligands CD80 and CD86 and blocks their interaction with the CD28 and CTLA-4 receptors expressed by T cells, therefore inhibiting T cell activation and function. Abatacept has shown clinical efficacy in treating some autoimmune diseases but has failed to show clinical benefit in other autoimmune conditions. The reasons for these disparate results are not clear and warrant further investigation of abatacept’s mode of action. Longitudinal spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 67 publications
1
65
0
Order By: Relevance
“…The observed effects could explain the poor efficacy in this cohort compared with reports on autoimmune conditions strongly associated with aberrant Tfh cell and plasmablast responses [49]. Further, a significant reduction in the relative frequency of CD45RO + memory Treg was detected [48]. These negative effects on Treg cells might impact the balance between effector and regulatory cell function and are detrimental to tolerance induction.…”
Section: Commentmentioning
confidence: 66%
See 3 more Smart Citations
“…The observed effects could explain the poor efficacy in this cohort compared with reports on autoimmune conditions strongly associated with aberrant Tfh cell and plasmablast responses [49]. Further, a significant reduction in the relative frequency of CD45RO + memory Treg was detected [48]. These negative effects on Treg cells might impact the balance between effector and regulatory cell function and are detrimental to tolerance induction.…”
Section: Commentmentioning
confidence: 66%
“…Interestingly, the cellular and molecular responses associated with abatacept therapy in both Treg and Tfh cells reversed upon discontinuation of treatment [48]. This reversal indicates that a co-stimulatory blockade does not lead to permanent reprogramming of these cells, providing a further explanation for why abatacept alone does not promote the development of sustained tolerance.…”
Section: Commentmentioning
confidence: 96%
See 2 more Smart Citations
“…Because Treg cells are largely specific for either auto-antigens or for components of the microbiome present on barrier surfaces, they are subject to chronic stimulation and many of the genes previously associated with Treg cells are activation-induced genes that are not actually Treg cell specific (Pesenacker et al, 2016). Consistent with this, among genes more highly expressed in Treg cells, several were genes we previously found to be downregulated in subjects treated with the co-stimulation blocking drug abatacept (CTLA4-Ig) (Glatigny et al, 2019), including ARHGAP11A, CENPE, DUSP4, ERI1, GXYLT1, HELLS, NUSAP1, PMAIP1, SGMS1, and TOP2A ( Supplementary Table 1). To account for these and other activationinduced genes, Pesenacker et al compared the transcriptomes of resting and activated Th and Treg cells, and identified a 31-gene 'activation-independent' Treg cell signature (Pesenacker et al, 2016).…”
Section: Th and Treg Cells Are Transcriptionally Distinctmentioning
confidence: 67%